Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3340/jkns.2010.48.4.354
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization of Completely Thrombosed Non-Giant Saccular Aneurysm Mimicking asDe NovoAneurysm

Abstract: J Korean Neurosurg Soc 48 : [354][355][356] 2010 Partial thrombosis of giant aneurysms is not uncommon however, complete angiographic occlusion occurs less frequently. In the case of non-giant aneurysms, complete thrombosis and recanalization has been rarely reported. A 31-year-old man presented to the emergency department with sudden bursting headache. Brain computed tomography (CT) revealed diffuse subarachnoid hemorrhage on the left side. Both CT angiography (CTA) and digital subtraction angiography show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“… 14) Although the pathophysiology of spontaneous recanalization has not been fully elucidated, recanalization ensuing from complete thrombosis of aneurysms has been reported in many studies. 4) 5) 11) 12) 16) 19) 21) 22) In these studies, recanalization of acute thrombosis of the aneurysm was observed in the days and weeks after thrombosis. Therefore, follow-up angiogram and careful observation during the follow-up period are required for fear of recanalization resulting in rebleeding of the aneurysm.…”
Section: Discussionmentioning
confidence: 90%
“… 14) Although the pathophysiology of spontaneous recanalization has not been fully elucidated, recanalization ensuing from complete thrombosis of aneurysms has been reported in many studies. 4) 5) 11) 12) 16) 19) 21) 22) In these studies, recanalization of acute thrombosis of the aneurysm was observed in the days and weeks after thrombosis. Therefore, follow-up angiogram and careful observation during the follow-up period are required for fear of recanalization resulting in rebleeding of the aneurysm.…”
Section: Discussionmentioning
confidence: 90%
“…The incidence of angiogram negative SAH is approximately 9-30% and 10% of repeat angiograms detect hidden aneurysms inducing SAH 1). The causes of angiogram negative SAH include thrombosed aneurysm, local vasospasm, parenchymal bleeding around an aneurysm, and high intracranial pressure 2). In this case, the authors suspected that thrombosis of the aneurysm occurred by hemostatic homeostasis after rupture to prevent further bleeding.…”
Section: Discussionmentioning
confidence: 93%
“…In this case, the authors suspected that thrombosis of the aneurysm occurred by hemostatic homeostasis after rupture to prevent further bleeding. Statistically 13-20% of giant aneurysms and 1-2% of non-giant aneurysms can be thrombosed, and the factors associated with thrombosis are a small aneurysmal neck, intraluminal thrombosis, and aneurysm age 2). The other possibility is focal vasospasm of the aneurysmal neck after rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation